Ossification of the Posterior Longitudinal Ligament in the Cervical, Thoracic, and Lumbar Spine - Barrios-Anderson, Adriel (Cureus, 2021)
Ossification of the posterior longitudinal ligament (OPLL) is a relatively rare disorder characterized by elongation of the posterior longitudinal ligament followed by the progressive development of ectopic osseous tissue along the ligament. OPLL is most commonly reported in the cervical spine, with fewer reported cases of thoracic or lumbar OPLL. The incidence of OPLL is high in east Asian populations with a much lower incidence in the United States. In this case report and review, we present the case of a 44-year-old female who was admitted to the hospital with a one-year history of progressive bilateral lower extremity weakness. Her lower extremity weakness had worsened over months and precipitated a gait disturbance that left her wheelchair-bound at the time of presentation. Additional presenting symptoms included lower back pain, stool incontinence, neck pain, and upper extremity paresthesias. Computed tomography of the spine revealed multiple areas of osteophyte formation and OPLL in the cervical spine from C2-5, thoracic spine from T6-10, and in the lumbar and sacral spine from L1-S1. There were notable areas of accompanying neural foraminal stenosis and central canal stenosis with visible spinal cord compression present in various locations. The patient did not undergo surgical intervention given the significant risk of multilevel surgery, and her symptoms were managed with medication. OPLL, particularly when not considered in lower-risk populations, can be a significant cause for progressive debilitating neurological abnormality. We report a rare case of OPLL occurring throughout the cervical, thoracic, lumbar, and sacral spine.